Synthesis, characterization, evaluation and molecular dynamics studies of 5, 6-diphenyl-1,2,4-triazin-3(2H)-one derivatives bearing 5-substituted 1,3,4-oxadiazole as potential anti-inflammatory and analgesic agents - Banerjee A.G.; Das N.; Shengule S.A.; Srivastava R.S.; Shrivastava S.K. (My University, 2025)
A series of triazin-3(2H)-one derivatives bearing 1,3,4-oxadiazole (4a-4o) were synthesized, characterized and evaluated for anti-inflammatory and analgesic activities. Preliminary in vitro anti-inflammatory activity was assessed using an albumin denaturation assay. The promising compounds were further evaluated in acute, sub-chronic and chronic animal models of inflammation. Derivatives 4d, 4e, 4g, 4j and 4l exhibited significant anti-inflammatory activity with reduced ulcerogenic, hepatotoxic and renotoxic liabilities compared to standard indomethacin. These potential derivatives were also evaluated for in vivo analgesic activity using a writhing model and the formalin-induced paw licking response in mice. Compounds 4d, 4e and 4g exhibited comparable analgesic activity, whereas 4j and 4l yielded moderate effects. The specificity of compounds 4d, 4e, 4g, 4j, and 4l to inhibit (cyclooxygenase-1) COX-1 and (cyclooxygenase-2) COX-2 isozymes and their kinetics were also determined via an in vitro COX inhibition assay. In silico docking studies were performed using a molecular dynamics simulation of the most active compound 4d (COX-2 IC50: 3.07 μM) at the COX-2 active site. The outcome of this exercise helped to verify the consensual interaction of these compounds with the enzyme. Copyright © 2015 Elsevier Masson SAS. All rights reserved.